A Multi-Criteria Fuzzy AHP Approach to Determine PKH Recipients in Sumber Harapan Village - Ade Amanda Yunita; William Ramdhan; Abdul Karim Syahputra (International Journal of Management Science and Information Technology, 2026)
The development of information technology encourages the use of decision support systems to increase objectivity and efficiency in various fields, including the determination of social assistance recipients. In addition, through the main discussion carried out in this study aims to be able to analyze the process of determining the recipients of the Family Hope Program (PKH) in Sumber Harapan Village based on predetermined social and economic criteria and applying the Fuzzy Analytical Hierarchy Process (Fuzzy AHP) method to determine the importance weight of each criterion so that the assessment process becomes more objective, systematic, and transparent. And in addition, for the Research Method section used in this study is a qualitative approach through direct observation, interviews with village officials and related parties, and documentation studies of prospective PKH recipient data. The results of the study indicate that the Fuzzy AHP method is effective in determining the priority of aid recipients based on seven assessment criteria. Of the 15 alternatives analyzed, Lina Marlina (Alternative 8) obtained the highest priority value of 0.0920, followed by Siti Aminah (Alternative 2) with a value of 0.0895 and Nabila Sari (Alternative 12) of 0.0876, while Dedi Kurniawan (Alternative 5) obtained the lowest value of 0.0349. The developed web-based decision support system is able to automate the data management process, Fuzzy AHP calculations and present selection results quickly and accurately, thus helping village governments produce more targeted, transparent and accountable decisions in the distribution of PKH social assistance.